2007
DOI: 10.1029/2006jd007487
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal and seasonal variations of inertial gravity wave activity in the lower atmosphere over central China

Abstract: [1] Gravity wave activities and background dynamical structure in the troposphere and lower stratosphere (TLS) over five stations at latitudes from 10°N to 40°N were statistically studied by using the data from Radiosonde observation on a twice daily basis at 0800 and 2000 LT. The background dynamical structure exhibits evident latitudinal and seasonal variations and has a profound influence on inertial gravity waves in the TLS. In the analyses of inertial gravity waves, according to the background structures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
92
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(114 citation statements)
references
References 40 publications
19
92
3
Order By: Relevance
“…The strongest northward wind occurs at 17.39 km in July, with a maximum value of 8.75 m s −1 , while the strongest southward wind occurs at 11.01 km in January, with a minimum value of −19.77 m s −1 . The characteristics of the background horizontal winds are similar to those revealed by radiosonde observations at middle latitudes (Zhang and Yi, 2007;.…”
Section: Data Descriptionsupporting
confidence: 67%
“…The strongest northward wind occurs at 17.39 km in July, with a maximum value of 8.75 m s −1 , while the strongest southward wind occurs at 11.01 km in January, with a minimum value of −19.77 m s −1 . The characteristics of the background horizontal winds are similar to those revealed by radiosonde observations at middle latitudes (Zhang and Yi, 2007;.…”
Section: Data Descriptionsupporting
confidence: 67%
“…Moreover, radiosonde observations usually have wide land coverage and long term accumulation, thus, multistation radiosonde observations should be favorable to reveal the latitudinal variation of GW energy densities. Up to now several multi-station radiosonde observations have been reported (Allen and Vincent, 1995;Wang and Geller, 2003;Wang et al, 2005;Zhang et al, 2006;Zhang and Yi, 2007;Gong et al, 2008). However, some limitations of these previous observations should be noted: 1) Narrow latitude coverage or too few stations were included.…”
Section: Introductionmentioning
confidence: 95%
“…Wang and Geller (2003) have investigated both E P and E K from 4 years (1998)(1999)(2000)(2001) of US high vertical resolution radiosonde observations over more than 90 stations and found that E T of stratospheric GWs have very large value sin winter in middle latitudes. Recently, Zhang and Yi (2007) analyzed the radiosonde observations from five stations located in latitudes of 20 • N-40 • N and found that although the E P has a maximum value at Haikou station (110 • 12 E, 20 • 12 N), which is in the lowest latitude among these five stations, the E K and E T exhibited maximum value in latitudes about 30 • N due to the strong tropospheric jet, which is thought to be an important GW source. Thus, a question arises: Do the kinetic energy and the total energy in the lower stratosphere really have completely identical latitudinal and seasonal variations as those of the potential energy?…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that satellites such as Microwave Limb Sounder (MLS) and Advanced Microwave Sounding Unit-A (AMSU-A) offer quantitative information of gravity waves in the middle atmosphere (Alexander and Rosenlof, 2003;Wu and Zhang, 2004;Zhang et al, 2013). In addition to satellite measurements, gravity waves are also observed by surface observations (Einaudi et al, 1989;Grivet-Talocia et al, 1999;Koppel et al, 2000), high-resolution radiosonde networks (Vincent and Alexander, 2000;Wang and Geller, 2003;Zhang and Yi, 2007;Gong and Geller, 2010), radars Worthington, 2000, 2007), and super-pressure balloons (Hertzog and Vial, 2001).…”
Section: Introductionmentioning
confidence: 99%